Comparing the Effects of Antiadhesive Materials after Abdominal Surgery - GÜNAL, ÖMER (DUZCE UNIV, 2020)
Objective: We aimed to evaluate and compare the effects of anti-adhesion materials, Seprafilm, Suprofilm, olive oil, and olive oil containing Vitamin E by measuring tension forces. Methods: 60 male Wistar-Albino rats were divided into six groups. The front side of the cecum and right abdominal parietal peritoneal wall were abrased. The rats were euthanized on the 14th postoperative day. Adhesions between intestines, omentum, other abdominal organs, cecum, incisionsites, and abdominal anterior wall peritoneum were all evaluated. Adhesion strength was measured with dynamometer. Histopathological evaluations of the adhesion area was performed. Results: Stage-I (0.43Newton) in Group-I, stage-IV (1.0540N) in Group-II, stage-II (0.6370N) in Group-III, stage-II in Group-IV (0, 5230N), stage-III (0.7620N) in Group-V, stage-IV (1.3560N) in Group-VI, were detected. A significant difference was found between these findings. P = 0.001, (p<0.05). Histopathological examination: It was found that GroupV-VI reduced inflammation, increased collagen production, fibroblastic activity and vascular proliferation. Conclusions: More objective evaluation can be made by measuring the tension force of the adhesions. Suprafilm can also be effectively used as an antiadhesive, such as Seprafilm. Olive oil and vitamin E require more studies to be used as antiadhesives.
Keywords: Antiadhesive; Tension force; Adhesion; Abdominal surgery; olive oil; SMALL-BOWEL OBSTRUCTION; VITAMIN-E; ADHESIONS